2022
DOI: 10.1002/bse.3049
|View full text |Cite
|
Sign up to set email alerts
|

Hey, did you see that label? It's sustainable!: Understanding the role of sustainable labelling in shaping sustainable purchase behaviour for sustainable development

Abstract: Consumers, nowadays, are becoming mindful of environmental issues than ever. The rising concerns for the adverse effects of consumption on environmental sustainability are leading to transformation in consumer behaviour. Consumers need relevant sustainability information about the products to shape sustainable purchase behaviours. On this note, marketers and organizations are increasingly using labels and logos for integrating sustainability evidence in their product offerings. This research integrates the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 118 publications
2
43
1
1
Order By: Relevance
“…Along with its predictive ability, the TBP is also known for its flexible structure. In the field of pro-environmental behaviour, to enhance its explanatory power and predictive ability in a specific context, authors extended the theory by introducing additional variables, such as environmental concern, environmental knowledge, and moral norms, along with the original three predictors of attitude, subjective norm, and perceived behavioural control (Yadav & Pathak, 2016;Dangelico et al, 2020;Siraj et al, 2022). Its flexible structure has further been applied with different variables, where new variables like environmental knowledge, eco-label knowledge, environmental concern, trust, norms, etc have been used along with few but not all the original predictors (Taufique et al, 2017;Dangelico et al, 2021;Tian et al, 2021).…”
Section: Theoretical Underpinning -The Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Along with its predictive ability, the TBP is also known for its flexible structure. In the field of pro-environmental behaviour, to enhance its explanatory power and predictive ability in a specific context, authors extended the theory by introducing additional variables, such as environmental concern, environmental knowledge, and moral norms, along with the original three predictors of attitude, subjective norm, and perceived behavioural control (Yadav & Pathak, 2016;Dangelico et al, 2020;Siraj et al, 2022). Its flexible structure has further been applied with different variables, where new variables like environmental knowledge, eco-label knowledge, environmental concern, trust, norms, etc have been used along with few but not all the original predictors (Taufique et al, 2017;Dangelico et al, 2021;Tian et al, 2021).…”
Section: Theoretical Underpinning -The Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%
“…claims surrounding environmental attributes communicated by the said label. The impact of trust on consumer decision-making or pro-environmental products is well established (Testa et al, 2015;Sharma, 2021) and research also states that trust plays an important role in the use of eco-labels for food purchase by consumers (Taufique et al, 2017;Gorton et al, 2021;Siraj et al, 2022). However extant research has measured 'trust' in general terms i.e.…”
Section: Belief In Environmental Ability Of Eco-labels and Willingnes...mentioning
confidence: 99%
“…The advent of quality assurance and process labels developed under a neoliberal paradigm where heightened hostility toward state intervention and regulation opened spaces for non-state actors (such as civil society and corporations) to participate in policy arenas (Rodrick, 2011; Clapp, 2012). A new role emerged for consumers to participate in the production side of economic systems through their ‘conscientious consumerism’ by way of knowledge about a product through quality assurance labels such as fair trade certified, non-GMO or environmentally friendly ‘green’ (Bain and Dandachi, 2014; Bartley et al ., 2015), with some now having a greater emphasis on ‘sustainable production’ (Autzen and Hegland, 2021; Burrows et al ., 2022; Siraj et al ., 2022). By emphasizing a products' quality attributes through labels, consumers can influence the demand (and thus the production) of products focused on social and environmental welfare by ‘voting with their dollars’.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental concern is a dominant cognitive component for studying purchase intentions for sustainable products (L. Zhang et al, 2019). Several studies have found that more positive environmental concern can lead to more positive attitudes, subjective norms and PBC towards sustainable products (Hartmann & Apaolaza-Ibáñez, 2012;Maichum et al, 2016;Rausch & Kopplin, 2021;Santos et al, 2021;Siraj et al, 2022;L. Zhang et al, 2019).…”
Section: Literature Review Theoretical and Conceptual Backgroundmentioning
confidence: 99%
“…Existing literature suggests that environmental concerns are a key factor influencing consumer decision-making processes regarding sustainable products (Diamantopoulos et al, 2003;Sharma & Foropon, 2019) In fact, environmental concerns are often seen as a key indicator of consumer environmental behaviour that directly influencing purchase intentions (Bamberg, 2003;Felix et al, 2018;Hartmann & Apaolaza-Ibáñez, 2012;Santos et al, 2021;Siraj et al, 2022;White & Simpson, 2013;Yue et al, 2022) The study by Testa et al (2020) showed that environmental concern might positively influence the purchase of sustainable packaging as green consumers actively search for environmental information. Park & Lin (2020) indicated that environmental concern has a positive impact on the intention to purchase recycled and upcycled fashion products.…”
Section: Environmental Concernmentioning
confidence: 99%